Prevalence of peripheral neuropathy in diabetes mellitus and its association with therapy, ethnicity and duration of diabetes mellitus - Karki, Dipesh; Nagila, Amar; Dhakal, Niraj; Chhetri, Sumit (Asian Journal of Medical Sciences, 2018)
Background: Diabetic peripheral neuropathy (DPN) is a most common micro vascular complication of diabetes posing significant morbidity and mortality with early and insidious onset. Studies has variably pointed that older age, gender, duration of diabetes, dyslipidemia, are linked with development of DPN. Aims and Objectives: To determine the prevalence of neuropathy in diabetic patients and see its link with age, gender, duration of diabetes, therapy and ethnicity. Materials and Methods: This is a cross-sectional study involving 110 clinically diagnosed diabetic patients, meeting the inclusion criteria. Basic demographic data were taken during clinical examination. Presence of degree of neuropathy was screened by measuring vibration perception threshold using Biothesiometer. Data was entered on SPSS and were categorized, necessary non parametric statistical tests were applied to these categorical variables as needed. The level of significance was set at p value less than 0.05. Results: Presence of neuropathy was measured in 110 diabetic patients. The overall prevalence of DPN was 45.45%. Frequency of neuropathy was higher with increase in age with 72.7% in more than 60 years of age and 23.5% in less than or equal to 40 years of age group (p=0.007). Similarly, the increasing trend of DPN with increase in duration of DM was evident in this study with DPN present in more than 55% of patients with more than 5 years of diabetes(p=0.004). Conclusion: The prevalence rate of DPN in diabetes was observed to be higher (45.45%). Our result suggested that DPN is associated with old age and the duration of diabetes mellitus. Asian Journal of Medical Sciences Vol.10(1) 2019 72-76